Modern technologies for assessing the performance effectiveness of the technical university department - Grigorash O. V. (PH "Sreda", 2018)
The scientific publication examines the theory and practice of assessing the performance of teachers, features of technical education, innovative technologies for assessing the effectiveness of teachers performance and the department of a technical university, including methods for assessing the quality of current student training, the quality of education of university graduates and the qualifications of teachers, and the conditions for implementing the proposed technologies. The monograph is intended for researchers engaged in the development of technologies that increase the objectivity of evaluating the performance of teachers and departments of a technical university, as well as employees of the administrative staff of universities and the Ministry of Science and Higher Education.
Keywords: эффективность работы; методика оценки; оценка качества; технологии оценки; кафедра технического вуза; техническое образование